2009
DOI: 10.1364/josaa.26.000b14
|View full text |Cite
|
Sign up to set email alerts
|

Approaching ideal observer efficiency in using color to retrieve information from natural scenes

Abstract: Variations in illumination on a scene and trichromatic sampling by the eye limit inferences about scene content. The aim of this work was to elucidate these limits in relation to an ideal observer using color signals alone. Simulations were based on 50 hyperspectral images of natural scenes and daylight illuminants with correlated color temperatures 4000 K, 6500 K, and 25,000 K. Estimates were made of the (Shannon) information available from each scene, the redundancies in receptoral and postreceptoral coding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…In one application [11], it was shown that coding at the receptors was highly redundant, as expected given the overlap of the spectral sensitivities of the medium-and long-wavelength-sensitive cone pigments [12]. But with optimal linear postreceptoral processing, redundancy was reduced and efficiency increased so that the information retrieved from color images of natural scenes under different daylight illuminants reached almost 90 percent of that achievable by an ideal observer.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In one application [11], it was shown that coding at the receptors was highly redundant, as expected given the overlap of the spectral sensitivities of the medium-and long-wavelength-sensitive cone pigments [12]. But with optimal linear postreceptoral processing, redundancy was reduced and efficiency increased so that the information retrieved from color images of natural scenes under different daylight illuminants reached almost 90 percent of that achievable by an ideal observer.…”
Section: Introductionmentioning
confidence: 93%
“…To provide a reference, the estimators were also applied to the cone photoreceptors of the human eye. Conveniently, mutual information can be interpreted as the logarithm of the mean number of distinct elements or points that can be identified without error across images of the scene under different illuminations [11], [14]. The resulting information estimates therefore provided an answer to the more specific question of the extent to which the elements of a scene can be identified by their colors, independent of spatial position.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was used in an offset form that converges more rapidly than the original [2,19]. The noise pdf f W was assumed, as elsewhere [4], to be Gaussian, with covariance matrix K determined by the SNR, which was set nominally to 100 [14].…”
Section: Differential Entropy Estimatorsmentioning
confidence: 99%